Do changes in brain neurotransmitter concentrations influence pacing strategy in the heat? - Roelands, B.; de Koning, J.; Foster, C.; Hettinga, F.; Meeusen, R. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Exercise-induced changes in the concentrations of dopamine, noradrenaline and serotonin have been linked to central fatigue (Roelands and Meeusen, 2010), with the most pronounced outcomes measured when exercise is performed in the heat. Little is known about the changes in pacing strategy induced by administration of central nervous system drugs acting on these neurotransmitter systems. Methods: Data were collected from 41 subjects (Wmax 341±37W). All subjects were endurance-trained cyclists and performed 60 min fixed intensity exercise (55% Wmax) followed by a time trial that was started at 75%Wmax, but subjects were free to change resistance. Environmental temperature was set at 30°C (relative humidity 50%). Power output was measured continuously and averaged in 5% intervals for statistical analysis. The pharmacological agents bupropion (2x300mg), methylphenidate (20 mg), reboxetine (2x8mg), citalopram (2x10mg) were compared to a placebo administration. Results: Methylphenidate and bupropion (mainly dopamine reuptake inhibitors, noradrenaline to a lesser extent) improved performance and increased core temperature, while no change in RPE and thermal comfort was apparent. The initial decrease in power output - observed in the placebo trial in the heat - was much smaller in the drug conditions. Reboxetine (noradrenaline reuptake inhibitor) significantly decreased performance. Power output during the reboxetine trials decreased more from the outset of exercise compared to the placebo situation. It remained parallel during the middle part of the time trial and was still lower during the end sprint. During the initial ten minutes of exercise, power output declined more in the citalopram trial (serotonin reuptake inhibitor); furthermore, subjects are unable to produce an end sprint after citalopram administration. Discussion/Conclusion: Dopaminergic drugs appear to override a central safety switch and allow athletes to use a reserve capacity that is not present in a normal (placebo) situation as it is a mean to avoid catastrophic outcomes. Manipulations of serotonin but most obviously noradrenaline have an opposite effect and force subjects to decrease power output early in the time trial. Despite the lower power output during the citalopram trial, subjects do not possess the drive and motivation to augment power output when approaching the end point.